Drawing as language: the systemic-functional semiotic argument. (3rd April 2019) - Riley, Howard
ABSTRACT: This article argues that drawing is a medium of visual communication, using any tool leaving a trace upon a surface, capable of referring to objects and events in the past, present and future, real and imaginary, functioning to modulate the viewer's attitude towards the subject-matter through the systematic selection and combination of visual elements according to cultural conventions which are subject to challenge, change and misunderstandings. In other words, I argue that drawing operates as language, defined in terms of systemic-functional semiotic theory. The theoretical basis is explained and discussed, with examples of the author's drawings demonstrating the theory as driver of creativity, facilitating the negotiation of meaning.